The Health Cost of Autocratization. Issue 5 (4th May 2022) - Son, Byunghwan; Bellinger, Nisha
Abstract: Are democratic crises also human crises? While the determinants of the erosion of democracy have been extensively scrutinised in the literature, their public policy consequences remain relatively unexplored. In a novel attempt to navigate this uncharted terrain, we analyse the effect of autocratization on health outcomes. We conceptualise autocratization as the relative decline of 'vertical' and 'horizontal' accountability. 'Vertical accountability' is threatened in the absence of regular free and fair elections as well as restricted political participation. A decline in vertical accountability lowers citizens' capacity to ensure governmental responsiveness to public demands. 'Horizontal accountability' is reduced when the executive branch undermines the other branches of government. Limited electoral competition further strengthens the executive branch relative to other branches. We argue that such a movement away from democracy – autocratization – has a detrimental effect on public health outcomes. We present empirical evidence supporting this argument in within- and cross-country contexts using regression discontinuity designs as well as panel data analysis.